Computational fluid dynamic simulations of solidification for enhancing speed of continuous cast copper - Thomas D.A. Jones (Engineering Science and Technology, an International Journal, 2021)
In this research experiment computational fluid dynamic (CFD) models were constructed, within Ansys Fluent TM v.R1, to investigate phenomena occurring during the Vertically Upwards Continuous Casting (VUCC) of 8 mm diameter, oxygen free copper (OFCu) for alterations to the casting speed. The simulated influence of heat transported over a 0.1 mm air gap formed within the casting die was investigated and a value for the die wall heat transfer coefficient (hc) of (9.0 ± 0.2) × 104 W/m2K, was extracted. Using this value for hc, simulations of the entire casting crucible and die were made for casting speed settings: pushback motion at 0.06 m/s, average; dwell motion (pause) at 0.05 m/s, average; and continuous motions at 0.022 m/s, 0.015 m/s and 0.008 m/s; and were validated against literature values for measured thermal distribution within the casting die. The fastest casting speed for 8 mm OFCu was investigated and a trend between simulated solidification front and measured grain growth direction was identified, highlighting, the casting motions pushback and dwell yield improved casting conditions. Fluid flow rate was investigated within the casting crucible and showed a small influence on casting due to natural convection relative to flow within the die, 0.001 ± 0.0005 m/s compared with 0.1 ± 0.01 m/s for pushback casting, respectively.